Calidad de cuidado de enfermería y satisfacción del paciente adulto mayor Hospital Belén de Trujillo - Baca Arteaga, Sahirita Katerinne (2020)
This descriptive, correlational cross-sectional research was carried out with the purpose of determining the relationship between the quality of nursing care and the satisfaction of the elderly patient of the medicine service of the Belen de Trujillo Hospital in a sample population of 90 patients, using the kendall tau c test for statistical analysis, concluding: 2.2% of older adults have a poor quality of nursing care, 22.2% regular, and 75.6% good. In the accessibility dimension, 10.0% of older adults are dissatisfied, and 90.0% of older adults are satisfied. In the dimension it explains and facilitates 13.3% of dissatisfied, and 86.7% of satisfied. In the dimension comforts 12.2% dissatisfied, and 87.8% satisfied. The dimension anticipates 12.2% dissatisfied, and 87.8% satisfied. In the dimension it maintains a relationship of trust, 18.9% of older adults are dissatisfied, and 81.1% satisfied. And in the dimension it monitors and tracks 15.6% dissatisfied, and 84.4% satisfied. There is a significant relationship between the level of quality of nursing care and the satisfaction of the adult patient in the medical service with a tau c value of kendall of 0.163 with a probability of 0.034